Sentiment Analysis of Gojek, Grab, Maxim Applications Using Support Vector Machine Algorithm - Muhammad Iqrom; M. Afdal; Rice Novita; Medyantiwi Rahmawita; Tengku Khairil Ahsyar (P3M Politeknik Negeri Bengkalis, 2025)
This research analyzes user sentiment towards three major online transportation applications in Indonesia—Gojek, Grab, and Maxim using the algorithm. The analysis results indicate that Maxim has the highest positive sentiment rate (42.45%) compared to Grab (32.83%) and Gojek (20.21%). Maxim's advantages lie in its competitive pricing and driver professionalism. However, Gojek recorded the best performance in sentiment classification with an accuracy of 94%, followed by Maxim (90%) and Grab (87%). The evaluation based on five main variables (general sentiment, drivers, services, applications, and pricing/costs) reveals the strengths of each application in different categories. Maxim excels in general sentiment and driver satisfaction, Grab dominates in pricing/cost, and Gojek stands out in the application category. Wordcloud visualization reveals frequently mentioned words such as